Pathophysiology of Lipid Metabolism in Chronic Renal failure patients - Najlaa Kadhim Ali; Fadheelah Salman Azeez; Dr.Abdullah Adil Raoof (Genius Publishing Group, 2025)
Assessing the main pathophysiological changes in individuals with chronic renal failure—which is characterized by either a persistent, substantial drop in glomerular filtration rate or a prolonged, irreversible loss of kidney tissue—is the aim of the study. It is also distinguished by a variety of clinical signs and indications as well as a broad spectrum of metabolic abnormalities.
Keywords: Pathophysiology; renal failure; lipid